(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Maize (Zea mays L.) is one of the world's most productive and prevailing crops. It is widely grown as human food and animal feed, as biofuel, and as a raw material for industry. Digestate and wood ash are the byproducts of cogeneration plants. Digestate is rich in nutrients, can provide plants with many nutrients required by the plant during its growing season, as well as improves the soil structure. The aim of the study was to determine the effect of the rates of digestate and wood ash mixture fertilizer on maize productivity and crop quality. In 2020, 2021 and 2022, in field trials with maize, the variety 'Hulk', FAO250, was used; the soil – sod-calcareous, medium-heavy sandy loam. Different variants of the mixture of cattle manure digestate and wood ash were used as a fertilizer on corn plantations. The ratios of digestate and wood ash was 1:0, 1:1, 2:1, and 3:1; fertilizer rates were 15 and 30 t ha-1. In the trial, different types of fertilizers demonstrated different effects on the yield and quality of maize. The use of the new fertilizers produced on average 36.93–38.33 t ha-1 of high-quality maize green mass in three years without using mineral fertilizers.